Data Mining Applications in Big Data - Lidong Wang; Guanghui Wang (Computer Engineering and Applications Journal, 2015)
Data mining is a process of extracting hidden, unknown, but potentially useful information from massive data. Big Data has great impacts on scientific discoveries and value creation. This paper introduces methods in data mining and technologies in Big Data. Challenges of data mining and data mining with big data are discussed. Some technology progress of data mining and data mining with big data are also presented.